Superhydrophobic anticorrosive coating for concrete through in-situ bionic induction and gradient mineralization. (10th October 2020) - Yin, Bing; Xu, Tianyuan; Hou, Dongshuai; Zhao, Erfa; Hua, Xianle; Han, Kailu; Zhang, Yue; Zhang, Jinrui
Graphical abstract: Highlights: A superhydrophobic concrete was fabricated through in-situ bionic mineralization. Molecular-scale modification of the concrete voids was controlled by organic matrix. The multistage gradient mineralization of calcite forms micro-nano hybrid structures. Abstract: Owing to the inherently multi-scale hydrophilicity of concrete, water and corrosive ions that may cause deterioration can easily adsorb to the surface through capillarity, and further penetrate into the interior of concrete. Superhydrophobic surface is one of the best choices for anti-corrosion, but it faces difficulties in durability and adaptability. This study reports a facile route to fabricate superhydrophobic concrete via in-situ biomineralization of inorganic crystals CaCO3 at specific sites controlled by organic matrix. Under the bionic induction of dopamine, the multi-stage gradient structure has been fabricated on calcite crystal, in which a micro-nano composite structure has been formed on the concrete surface. The induction mechanism is explained by the density functional theory. The structure, composition and topological features of the prepared nano-coatings have been characterized by various surface analysis techniques. After modified by silane, the superhydrophobicity and hydrophobic stability of the surface has been confirmed by its large contact angle (CA = 156 ± 3°) and its stability under water, being attributed to the modified concrete voids, the surface micro/nanostructures and a silane layer on them.